Эффект стимуляции репаративных процессов под влиянием фракции до 5 кДа из пуповинно-плацентарной крови крупного рогатого скота - Гулевский, А.К.; Грищенко, В.И.; Моисеева, Н.Н.; Абакумова, Е.С.; Никольченко, А.Ю.; Щенявский, И.И.; Долгих, О.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
The wound and ulcer healing activity of the 5 kDa fractions derived from cord blood and the sugar-decreasing activity, which apparently promotes the glucose utilization by cells, are shown. This improves the cell energy status and makes an impact on the functional cell metabolism. Therefore, the acceleration of reparation processes in the field of burning wounds and ulcer occurs. The analogous fraction derived from adult cows does not reveal such effects.